MEMBUDAYAKAN LITERASI PADA ANAK USIA DINI DENGAN METODE MENDONGENG - Lilis Sumaryanti (AL-ASASIYYA: Journal Of Basic Education, 2018)
In an increasingly sophisticated era of globalization, the challenges of the times demand that all be developed, including having broad knowledge and knowledge and supported by positive habituation, namely by cultivating literacy in everyday life. The process of introducing and planting literacy must begin at an early age so that this habituation can be inherent in each individual. Consumptive souls who want everything to be instantaneous by utilizing certain tools to simplify work and can make time efficient become obstacles for the community to cultivate literacy. This problem causes the reading interest of the next generation to decline. Literary works have been known since ancient times. Evidenced by the many works that have been produced, one of them is a fairy tale. Fairy tales are literacy works produced by previous ancestors as a form of literary culture. The creation of this tale is an effort to move the culture of literacy of the next generation. Literacy culture by reading fairy tales is an effort of parents to help early childhood in developing self-potential and teach life experiences because in the "golden age" children develop in imitation.